Orientasi Teknologi Pendidikan Dalam Perspektif Peningkatan Kreativitas Guru Pada Proses Pembelajaran - Medi Yansyah; Aji Raditya; M. Tafsiruddin; Siti Rochmatun; Putri Agustina; Anggitya Alfiansari (Journal on Education, 2023)
Educational technology in its development can be viewed as both a product and a process. As a product, educational technology is easier to understand because of its concrete nature. Educational technology at a macro level aims to encourage and provide direction to teachers to view teaching actions as an effort to solve problems scientifically. The concept of educational technology is expected to increase the quality of education, especially for teachers, so that they will have a more solid grip and reliable guidelines for providing good teaching. more effective. The main key to the success of these goals is at least the teacher as a central figure as well as one of the human beings who is responsible for the continuity of the existing educational process in preparing students who have quality (bari) from the learning process they get. For this reason, it is necessary to improve the attitude of the teacher's abilities, in this case the demand for the creativity of a teacher in imparting (transferring) his knowledge towards the learning process that is currently being faced.